Analytical Method Development on Impurity Profiling and Category Wise Analytical Perspectives of Antidiabetic Drugs: A Review - Mahesh M. Deshpande; Madhuri H. Bhalerao (Pharmaceutical Research - Recent Advances and Trends Vol. 3, 2024)
According to ICH Q3A(R), the impurity in a new drug substance is “any component of new drug substance that is not the chemical entity defined as new drug substance”. As Per ICH Q3B(R), the impurity in the new drug product is “any component of the drug product that is not the drug substance and excipients in the drug product.” There are a number of spectroscopic methods that include Ultraviolet spectroscopy, Mass spectroscopy, Nuclear magnetic resonance spectroscopy and Chromatographic methods including HPLC, HPTLC, GC, and UPLC used for the identification and characterization of impurities in API and drug products. As well as hyphenated techniques like LC-MS, LC/ESI-MS, and LC-NMR-MS are used for impurity profiling of the drug. Forced degradation studies are used to facilitate the development of analytical methodology, to achieve a better understanding of drug substance and drug product stability, and to determine degradation pathways and degradation products. This study will help to get a stable formulation. This review describes the number of impurities identified in the pharmaceutical drugs and the drug products used to treat type 2 diabetes. The impurities are classified according to ICHQ3A (R2) guidelines along with their identification. We delineate the impurity profiling of anti-diabetic drugs (Oral hypoglycemic agents) categories as Dipeptidyl peptidase-4 inhibitors, K-ATP channel blockers, Sulfonylureas, Alpha-Glucosidase inhibitors, Sodium-glucose co-transport-2 inhibitors, Biguanide and Thiazolidinedione.